From the soap opera script to the travel itinerary: an analysis of cinematographic tourism in the soap opera Fuzuê - Goldoni, Giulia (Aprender, 2024)
This article proposes a reflection on the imaginaries that the soap opera Fuzuê, from the Globo network, brings in relation to the shightseeings of Rio de Janeiro. The research aims to understand how Globo presents these tourist attractions and if there is  any incentive to visit these places. The analysis is mainly based on a bibliographical bias, supported by some reports collected on social networks in which the soap opera and tourist attractions are mentioned. The guiding question of the research was: "What are the imaginaries of Rio de Janeiro's tourist attractions presented in the soap opera Fuzuê?" The analysis took place in relation to three tourist attractions most shown in the soap opera, these being: Arcos da Lapa, Real Gabinete Português de Leitura and the Neighborhood of Fátima. From there, it was possible to conceive a reflection that shows that the way in which the Globo network presents these points reinforces an imaginary that is more idealistic than reality, in fact, distancing cinematographic tourism in these spaces.
Keywords: cinematographic tourism; tourist spots; soap opera